Rare and unusual clinicopathologic presentation of renal AL amyloidosis. (5th April 2016) - Logan, Andrew; Zuppan, Craig; Pi, Alexander; Zhang, Zhiwei; Jaipaul, Navin
Lesson: Rarely, renal light chain (AL) amyloidosis may present without significant proteinuria owing to glomerular sparing and amyloid deposition confined to the vasculature and tubulointerstitium.